1990
DOI: 10.1126/science.2108497
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Resistance to Alkylating Agents Conferred by Mechanisms Operative Only in Vivo

Abstract: EMT-6 murine mammary tumors were made resistant to cis-diamminedichloroplatinum (II) (CDDP), carboplatin, cyclophosphamide (CTX), or thiotepa in vivo by treatment of tumor-bearing animals with the drug during a 6-month period. In spite of high levels of in vivo resistance, no significant resistance was observed when the cells from these tumors were exposed to the drugs in vitro. The pharmacokinetics of CDDP and CTX were altered in animals bearing the respective resistant tumors. The resistance of all tumor lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
150
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 285 publications
(157 citation statements)
references
References 16 publications
6
150
0
1
Order By: Relevance
“…Tofilon et al 26 reported the enhancement of spontaneous metastasis of a hepatocarcinoma growing intramuscularly following administration of a single dose of BCNU. Teicher et al 27 established 4 alkylating agent-resistant variants of a murine mammary tumour cell line, EMT-6, in vivo by repeated treatment of tumour-bearing mice with CPT, carboplatin, cyclophosphamide or thiotepa. These drug-resistant cell lines (particularly the CPT-resistant variant) were much more efficient at forming spontaneous lung metastases after s.c. injection of cells in comparison to the drug-sensitive parental line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tofilon et al 26 reported the enhancement of spontaneous metastasis of a hepatocarcinoma growing intramuscularly following administration of a single dose of BCNU. Teicher et al 27 established 4 alkylating agent-resistant variants of a murine mammary tumour cell line, EMT-6, in vivo by repeated treatment of tumour-bearing mice with CPT, carboplatin, cyclophosphamide or thiotepa. These drug-resistant cell lines (particularly the CPT-resistant variant) were much more efficient at forming spontaneous lung metastases after s.c. injection of cells in comparison to the drug-sensitive parental line.…”
Section: Discussionmentioning
confidence: 99%
“…These drug-resistant cell lines (particularly the CPT-resistant variant) were much more efficient at forming spontaneous lung metastases after s.c. injection of cells in comparison to the drug-sensitive parental line. 28,29 Using the method of Teicher et al, 27 Mitsumoto et al 30 established 2 CPTresistant mouse epithelial tumour cell lines with enhanced metastatic capabilities associated with higher levels of cell adhesion to ECM components, such as fibronectin, laminin, collagen type IV and Matrigel; enhanced MMP-2 activity; and higher levels of cell motility. Van Putten et al 31 showed that treatment of animals bearing a transplantable osteosarcoma with cyclophosphamide or CCNU resulted in a significant increase in lung metastases compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance observed was reversible after discontinuation of treatment, as demonstrated in our model. In spite of high levels of resistance in vivo, no significant resistance was observed when the cells from these tumours were exposed to the drugs in vitro, indicating that a very high level of resistance to anticancer drugs can develop through mechanisms that are exclusively in vivo (Teicher et al, 1990). Furthermore, Kobayashi et al (1993) have suggested that some forms of acquired drug resistance operate only at the multicellular level, as opposed to classic unicellular resistance mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…To identify genes overexpressed in cyclophosphamideresistant EMT6/CTX mouse mammary tumor cells relative to sensitive parental EMT6 cells, 14 suppression-subtractive hybridization was performed using a PCR-Select kit (Clontech, Palo Alto, CA) and products were cloned and sequenced. BLAST analysis 15 (web address: http:// www.ncbi.nlm.nih.gov/BLAST) of one of the sequences revealed that it was identical to mouse SPF45 1 (GenBank AF083384).…”
Section: Cloning Of Spf45 Cdnamentioning
confidence: 99%